ENHANCEMENT OF FINISHED GOODS ACCOUNTING IN MANUFACTURING COMPANIES IN COMPLIANCE WITH INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) - Pashakhodjayeva Dildora Dzhabborkhonovna,; Niyazova Firuza Komiljon qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. The article examines ways to enhance finished goods accounting in manufacturing companies in accordance with International Financial Reporting Standards (IFRS). It analyzes key accounting issues related to recognition, measurement, and reporting of finished products. The study proposes recommendations to improve accounting transparency and compliance.